PENGEMBANGAN ADOPSI INOVASI MELALUI JARINGAN KOMUNIKASI - Ellyta Ellyta; Uray Mustakim; Rahmatullah Rizieq (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Acceleration of innovation adoption can be done if the communication network patterns in farmer groups are known. The research was conducted at The Citrus Production Center in Sambas District, West Kalimantan. Farmer group samples were taken 15 groups randomly while farmer sampling was done with the Representative Sample of Intact System. The structure and role of farmers in communication networks were analyzed by communication network analysis from Rogers and Kincaid and relationship analysis with Rank Spearman method. The results showed the structure of communication, in terms of the level of connectedness of farmers in the group was low while the openness of farmer groups was high. The higher the involvement and openness of farmers in the communication network, the better behavior of farmers in marketing. In addition, the pattern of communication networks that are formed is the pattern of wheels, namely the role of leaders in groups (star) plays an important role in the distribution of information in farmer groups. The other results were efforts to overcome the marketing problems that occur in farmers, namely by delaying the harvest and delay selling.